"Authorship Prevails in Nurseries": Alice Meynell as Mother, Mentor, and Muse. Issue 2 (3rd April 2019) - Bunting, Kirsty
ABSTRACT: Viola Meynell was raised in an at-home magazine office and trained in aestheticist poetry of the 1890s by her mother, Alice Meynell. Making use of extensive and previously unpublished correspondence between Alice and Viola from the Meynell family archive, this essay charts Viola's rebellious turn towards the novel form and early experimental modernism, and her rebellion's impact on the mother–daughter relationship. The two women wrote about each other in myriad poetry, essays, fiction, and biography, and, when read side by side, these writings offer an intriguing picture of their lives together and trace alternating periods of generational distance and intimacy. Specifically, the article traces Alice's reification in print as ideal wife, mother, and homemaker, and contrasts this ideal with Viola's daily observations of her mother. Before and after Alice's death, Viola fought to demythologize, reclaim, celebrate, and mourn the real Alice Meynell in her work, while her own literary reputation was damaged by her association with the domestic and her prolonged apprenticeship under her mother.